Global anomie, dysnomie, and economic crime: hidden consequences of neoliberalism and globalizaiton in Russia and around the world - Passas, Nikos (Social justice, 2000)
Part of a special issue on criminal justice at the new millennium. The writer argues that neoliberalism and globalization add to processes leading to global anomie, dysnomie, and ultimately, economic crime. He clarifies the basic concepts and outlines the theoretical framework that has been used in the analysis of U.S. organizational and individual deviance. He presents the main characteristics of globalization and neoliberalism and contrasts the claims made by supporters of neoliberal policies and the actual outcomes of the policies in Russia. He also demonstrates how these outcomes affect crime in Russia. In conclusion, he examines the fundamental policy implication that his analysis reveals.